(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article studies the problem of monotonous speech that many learners of English as a second language face, and suggests ways to overcome it through a comparative analysis of the rhythmic features of English and Russian. Intonation is not only the tone of speech, but also an important tool for expressing meaning, emotions, and communicative intentions. The study explains that one of the main differences between the two languages is their rhythm: English is stress-timed, while Russian is more syllable-timed. Because of this difference, learners often transfer patterns from their native language into English. This process, known as intonational interference, makes speech sound unnatural, flat, or robotic. As a result, communication can become less effective or even unclear. To solve this problem, the article suggests practical teaching strategies such as speech shadowing, rhythmic mapping, and focused pronunciation practice. These methods help learners develop a better sense of rhythm and natural intonation. In conclusion, systematic work on intonation plays a key role in improving learners’ communicative competence and making their speech more natural and understandable.